2020
DOI: 10.1039/d0ta01893g
|View full text |Cite
|
Sign up to set email alerts
|

Over 14% efficiency nonfullerene all-small-molecule organic solar cells enabled by improving the ordering of molecular donors via side-chain engineering

Abstract: Improving the short-circuit current density (Jsc) is a big challenge for gaining highly efficient nonfullerene all-small-molecule organic solar cells (NFASM-OSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…While it is indeed well established that the use of additional hole transporting layers (BPAPF) and extraction/injection barriers (BPAPF doped with NDP9/NDP9) has a beneficial effect on the FF, such values, amongst the highest reported so far, 19,31 have been barely achieved in all-small molecule OSCs. [32][33][34][35][36] The characterization of PHJ cells fabricated by thermal evaporation has revealed very high FF values consistent with the high hole mobilities measured for the donor materials.…”
supporting
confidence: 64%
“…While it is indeed well established that the use of additional hole transporting layers (BPAPF) and extraction/injection barriers (BPAPF doped with NDP9/NDP9) has a beneficial effect on the FF, such values, amongst the highest reported so far, 19,31 have been barely achieved in all-small molecule OSCs. [32][33][34][35][36] The characterization of PHJ cells fabricated by thermal evaporation has revealed very high FF values consistent with the high hole mobilities measured for the donor materials.…”
supporting
confidence: 64%
“…With further device optimizations of controlling the prepared solution concentration or fabricating ternary devices using PC 71 BM, the efficiencies are further promoted to 14.7% 80 and 15.34% 39 (certified at 14.7%), respectively. Besides, the fluorination molecules BSFTR 81 and BT‐2F 82 also show low‐lying HOMO levels and enhanced crystallinity, and their corresponding devices using Y6 acceptor exhibit impressive PCEs around 14% (Figure 5).…”
Section: Smds Based On Benzodithiophene Unitmentioning
confidence: 99%
“…The length and arrangement of alkyl chains in the π‐bridge can influence their solubility, planarity, and packings. Compared to BTEC‐2F, BT‐2F has shorter and more regulate hexyl chains in the terthiophene bridge, and thus achieves better molecular packing and enhanced photovoltaic performance 82 . The different hexyl chain positions in the 2‐(thiophen‐2‐yl)thieno[3,2‐b]thiophene bridge of BOHTR and BIHTR bring about changes in their backbone planarity, molecular packing and mixing feature with acceptor Y6 89 .…”
Section: Smds Based On Benzodithiophene Unitmentioning
confidence: 99%
“…8,23,24 However, SM donors sporadically succeeded with several advantages such as high crystallinity, rapid aggregation pathways, controllable energy levels, etc., and as a result, assisting the significant enhancement of PCEs in recent years. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] However, the combination of a SM donor and a SM acceptor has been a bottleneck hindering the performance so far due to their high crystallinity and unfavourable phase separation and morphologies. 25,39 Recently, Wei et al reported an A-p-D-p-A structural narrow bandgap SM donor based on a larger coplanar core DTBDT and achieved the highest PCE of 14.34% at that time for binary all SM OSCs by optimizing their hierarchical morphologies.…”
Section: Introductionmentioning
confidence: 99%